Understanding pedagogic documentation in early childhood education : revealing and reflecting on high quality learning and teaching - Formosinho, João; Peeters, J. (Routledge, 2019)
Much more than simply recording events, pedagogical documentation is a revolutionary educational approachthat enables practitioners to capture and understand the ways in which children learn and think. Exploring the use of pedagogic documentation across five different cultures, this book offers a unique insight into the conditions and methods through which pedagogical documentation might become an effective means of connecting teaching and learning. By drawing on theory, research-based evidence and practice, Understanding Pedagogic Documentation in Early Childhood Education reveals pedagogic documentation as an instigator for critical reflection on practice, for the creation of new pedagogical approaches and improvements in quality. Observing and documenting the lived educational experience of children and practitioners is emphasised as a means of acknowledging their voice and rights, of revealing their knowledge, their competences, their attitudes and dispositions to learning. Offering contextualised approaches and considering the challenges involved in observing and documenting day-to-day practice in early childhood settings, chapters encourage professionals to reflect and recognise the value of documentation for children, staff members and the wider community. Making a crucial contribution to the debates on pedagogical documentation, Understanding Pedagogic Documentation in Early Childhood Education offers researchers, students, policy-makers and professionals a comprehensive, and multicultural perspective on pedagogical documentation.- Resumé vydavatel
Keywords: předškolní výchova; dokumentace; pedagogická evaluace; preschool education; documentation; educational evaluation; elektronické knihy; sborníky; electronic books; papers of several authors